2014
DOI: 10.1371/journal.pone.0096571
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation Therapy Prior to Diagnosis Induced Primary Osteosarcoma Metastasis—From Clinical to Basic Research

Abstract: Osteosarcoma (OS) patients who suffer manipulation therapy (MT) prior to diagnosis resulted in poor prognosis with increasing metastasis or recurrence rate. The aim of the study is to establish an in vivo model to identify the effects of MT on OS. The enrolled 235 OS patients were followed up in this study. In vivo nude mice model with tibia injection of GFP-labeled human OS cells were randomly allocated into MT(+) that with repeated massage on tumor site twice a week and no treatment as MT(−) group. The five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
1
25
0
2
Order By: Relevance
“…In addition, silencing PREX2a expression suppressed OS cell proliferation, migration and invasion. MMP2 and MMP9 have been suggested to participate in the metastasis of OS (24), and the expression and activity of MMP2 and MMP9 are tightly associated with OS cell migration and invasion (25)(26)(27). The present study demonstrated that suppression of PREX2a notably inhibited the invasion and migration of OS cells, at least partly via suppressing the protein expression of MMP2 and MMP9.…”
supporting
confidence: 58%
“…In addition, silencing PREX2a expression suppressed OS cell proliferation, migration and invasion. MMP2 and MMP9 have been suggested to participate in the metastasis of OS (24), and the expression and activity of MMP2 and MMP9 are tightly associated with OS cell migration and invasion (25)(26)(27). The present study demonstrated that suppression of PREX2a notably inhibited the invasion and migration of OS cells, at least partly via suppressing the protein expression of MMP2 and MMP9.…”
supporting
confidence: 58%
“…Up to now, the pathogenesis and tumor driver genes of osteosarcoma have not been clarified, and the main treatment for osteosarcoma is surgery, chemotherapy, and adjuvant chemotherapy 22 . However, 40% of patients with osteosarcoma are at risk of pulmonary metastasis and recurrence, with a 5-year survival rate of only 20% 23,24 . Therefore, target therapy is a promising clinical treatment for osteosarcoma 25 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the presence of labeled epithelial cells in sentinel axillary nodes in patients with breast cancer was found to be increased in patients who underwent breast massage prior to the procedure (60). Although this was interpreted as a form of "benign mechanical transport," similar to that occurring with needle biopsies, rather than true micrometastases (61), there is a remaining debate on the long-term risks associated with such findings (62,63). There is also controversy over the role and safety of manual therapies and acupuncture in the management of lymphedema postcancer treatment (64,65).…”
Section: Potential Effects Of Physical-based Treatments On Cancermentioning
confidence: 99%